2016
DOI: 10.1089/neu.2015.4079
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of the Glutamate Transporter Activator (R)-(−)-5-methyl-1-nicotinoyl-2-pyrazoline (MS-153) following Traumatic Brain Injury in the Adult Rat

Abstract: Traumatic brain injury (TBI) in humans and in animals leads to an acute and sustained increase in tissue glutamate concentrations within the brain, triggering glutamate-mediated excitotoxicity. Excitatory amino acid transporters (EAATs) are responsible for maintaining extracellular central nervous system glutamate concentrations below neurotoxic levels. Our results demonstrate that as early as 5 min and up to 2 h following brain trauma in brain-injured rats, the activity (V max ) of EAAT2 in the cortex and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 90 publications
3
27
0
Order By: Relevance
“…Previous work has shown that the levels and/or function of EAAT2 (rodent analog, GLT-1), the most abundantly expressed glutamate transporter in hippocampal astrocytes (Maragakis and Rothstein, 2006) are reduced in conjunction with A␤ pathology and/or glial activation (Masliah et al, 1996;Abdul et al, 2009;Simpson et al, 2010;Tian et al, 2010;Scimemi et al, 2013;Hefendehl et al, 2016). AAV-mediated delivery of VIVIT to 5xFAD mice reduced both A␤ plaque load in CA1 (Fig.…”
Section: Aav-gfa2-vivit Reduces A␤ Pathology and Increases Glt-1 Exprmentioning
confidence: 89%
See 4 more Smart Citations
“…Previous work has shown that the levels and/or function of EAAT2 (rodent analog, GLT-1), the most abundantly expressed glutamate transporter in hippocampal astrocytes (Maragakis and Rothstein, 2006) are reduced in conjunction with A␤ pathology and/or glial activation (Masliah et al, 1996;Abdul et al, 2009;Simpson et al, 2010;Tian et al, 2010;Scimemi et al, 2013;Hefendehl et al, 2016). AAV-mediated delivery of VIVIT to 5xFAD mice reduced both A␤ plaque load in CA1 (Fig.…”
Section: Aav-gfa2-vivit Reduces A␤ Pathology and Increases Glt-1 Exprmentioning
confidence: 89%
“…High-speed measures of fluctuating L-glutamate levels in intact mice were performed using ceramicbased microelectrode arrays (MEAs) as previously described (Hascup et al, 2007(Hascup et al, , 2011Miller et al, 2015). The W4 type MEAs (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations